Regional hydrothermal alteration mapping using landsat-8 data - Pour, Amin Beiranvand (2015)
This study evaluates the capability of Earth Observing-1 (EO1) Advanced Land Imager (ALI) data for hydrothermal alteration mapping in the Meiduk and Sar Cheshmeh porphyry copper mining districts, SE Iran. Feature-oriented principal components selection, different and band ratioing were applied for enhancing the hydrothermally altered rocks associated with porphyry copper mineralization, lithological units and vegetation using ALI data. Mixture-tuned matched-filtering (MTMF) were tested to discriminate the hydrothermal alteration areas of porphyry copper mineralization from surrounding environment using shortwave infrared bands of ALI. Results indicated that the tested methods are able to yield spectral information for identifying vegetation, iron oxide/hydroxide and clay minerals, lithological units and discrimination of hydrothermally altered rocks from unaltered rocks using ALI data at regional scale. The achievements of this investigation indicate considerable implications for geologists to use Earth Observing-1 (EO-1) ALI data for geological purposes.